Pipeline flow diverter and transvenous coiling for the treatment of direct carotid cavernous sinus fistulae: a retrospective case series - Omar Abu-Fares; Antonis Adamou; Heinrich Lanfermann; Joachim K. Krauss; Shadi Al-Afif; Katja Döring (CVIR Endovascular)
Abstract Background Carotid cavernous fistulae (CCF) are pathological connections between the carotid arteries and the cavernous sinus. Endovascular procedures are the mainstay treatment for CCF. The aim of this report is to evaluate the efficacy and safety of the combined use of the Pipeline Vantage (PV) flow diverter and transvenous coil embolization in the treatment of CCF. Methods Retrospective,monocentric analysis of three patients who underwent neurointerventional treatment of clinically symptomatic CCF using a combination of transvenous coil embolization and flow diverter Implantation. Clinical data, the etiology of the CCF and clinical and radiological follow up were evaluated. Results Clinical and radiological follow-up were available at 3 and 12 months. One patient experienced clinical improvement immediatley after the interventions. The other two patients improved within one year after treatment. No symptomatic complications were recorded. One year after the intervention complete CCF occulsion was documented in all cases. Conclusions We report an initial experience for the treatment of direct CCF using the combination of a new generation Pipeline FD and transvenous coil embolization. The high treatment success rate and low complication rate are encouraging.